Citizen-to-Soldier-to-Citizen and Cyber Warrior: Building the Cybersecurity Workforce with Military Veterans (Journal of The Colloquium for Information Systems Security Education, 2015)
The cyber threats facing America have escalated sharply in recent years and has emerged as a clear and present danger to the nation's homeland and national security, economic prosperity, intellectual capital, and critical infrastructure. In the face of such persistent and escalating cyber threats, the United States is determined to immediately develop the capability necessary to counter this threat. A key component of the national cybersecurity strategy includes building a qualified cybersecurity workforce with the competence, knowledge, and technical skills. The cyber workforce must be capable when necessary to not only respond to, effectively counter, and eventually prevent the occurrence of cyber attacks. This paper argues that the U.S. has an untapped resource that will enhance its ability to meet the cybersecurity workforce requirements. That resource is the available military veterans who have served this country with distinction and honor. Most veterans have demonstrated through their service that they possess the necessary potential, characteristics and experience to successfully participate in the cybersecurity workforce. This paper postulates that the cybersecurity workforce can be rapidly filled by focusing efforts on the recruitment, education, and employment of military veterans.
Keywords: military veterans; cybersecurity; cyber threats; national security; cybersecurity workforce